Peran Pelatihan dan Pengembangan Karyawan Dalam Meningkatkan Pelayanan pada Hotel Zartin Syariah Ujung Gading Sumatera Barat - Muhammad Fayyadh; Uswah Hasanah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The objective of this study is to investigate the impact of staff training and development on enhancing the quality of services provided at the Zartin Syariah Hotel Ujung Gading, located in West Sumatra. Field study using an observational and interview-based qualitative descriptive technique is the research methodology used. The study's findings demonstrate that the hotel has recognized issues and taken proactive measures to enhance the quality of its services, particularly by investing in the professional growth and training of each worker with an emphasis on sharia principles. Regular evaluation, employee motivation, reward, punishment, collaboration, and feedback from guests are also important elements in a hotel's efforts to improve service quality. Keywords: Training, Development, Service